2012
DOI: 10.1007/s00221-012-3070-3
|View full text |Cite
|
Sign up to set email alerts
|

Motor map reliability and aging: a TMS/fMRI study

Abstract: This study compared the reliability of motor maps over 3 sessions from both neuronavigated transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) data between younger and older adults. Seven younger (ages 19-31) and seven older (ages 64-76) adults participated in three joint TMS/fMRI assessment sessions separated by 7 or 14 days. Sessions involved mapping of the right first dorsal interosseous muscle using single-pulse TMS immediately followed by block-design fMRI scanning inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 47 publications
5
34
1
2
Order By: Relevance
“…More specifically, the high reliability, captured by the intraclass correlation (ICC), of the RMT and mean map MEP amplitude confirmed previous findings following shorter observation periods [4953]. Former findings on the consistency of the CoG were more variable [15, 48, 51, 53] than the high reliability in the present study for observation periods of up to 1.5 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More specifically, the high reliability, captured by the intraclass correlation (ICC), of the RMT and mean map MEP amplitude confirmed previous findings following shorter observation periods [4953]. Former findings on the consistency of the CoG were more variable [15, 48, 51, 53] than the high reliability in the present study for observation periods of up to 1.5 years.…”
Section: Discussionsupporting
confidence: 91%
“…Former findings on the consistency of the CoG were more variable [15, 48, 51, 53] than the high reliability in the present study for observation periods of up to 1.5 years.…”
Section: Discussioncontrasting
confidence: 54%
“…Using this approach, intersession reliability of motor-related activation in this study was found to be comparable to previously published results for both spatial overlap and ICC measures (Bennett and Miller, 2010; Gountouna et al, 2010; Havel et al, 2006; Kong et al, 2007; McGregor et al, 2012; Yoo et al, 2005). This supports the validity and appropriateness of the analytical approach used in this study to assess intersession reliability of pain-related fMRI activation.…”
Section: Discussionsupporting
confidence: 89%
“…High test-retest reliability of fMRI responses across two or more sessions has been reported for a wide variety of tasks, including motor, auditory detection, language, learning, and memory (Atri et al, 2011; Bennett and Miller, 2010; Cacares et al, 2009; Chen et al, 2007; Fliessbach et al, 2010; Freyer et al, 2009; Gorgolewski et al, 2013; Gountouna et al, 2010; Havel et al, 2006; Kiehl and Liddle, 2003; Maitra et al, 2002; McGregor et al, 2012; Yoo et al, 2005). However, poor test–retest reliability of fMRI responses has been found for other tasks such as mouth movements (Havel et al, 2006), reward (Fliessbach et al, 2010), and spatial attention (Gorgolewski et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported relationships between fMRI and TMS in healthy subjects. It has been shown that fMRI activation is positively related to corticomotor output maps, 38 while BOLD fMRI signal intensity of activation is related to TCI. 39, 40 With chronic stroke patients, it has been shown that reduced fMRI laterality to the ipsilesional hemisphere relates to smaller motor evoked potentials.…”
Section: Discussionmentioning
confidence: 99%